Synthesis, characterization and luminescence studies of gold(I)–NHC amide complexes - Gómez-Suárez, Adrián; Nelson, David J.; Thompson, David G.; Cordes, David B.; Graham, Duncan; Slawin, Alexandra M. Z.; Nolan, Steven P. (Beilstein Journal of Organic Chemistry, 2013)
A flexible, efficient and straightforward methodology for the synthesis of N-heterocyclic carbene gold(I)–amide complexes is reported. Reaction of the versatile building block [Au(OH)(IPr)] (1) (IPr = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) with a series of commercially available (hetero)aromatic amines leads to the synthesis of several [Au(NRR’)(IPr)] complexes in good yields and with water as the sole byproduct. Interestingly, these complexes present luminescence properties. UV–vis and fluorescence measurements have allowed the identification of their excitation and emission wavelengths (λmax). These studies revealed that by selecting the appropriate amine ligand the emission can be easily tuned to achieve a variety of colors, from violet to green.
Keywords: fluorescence; gold; gold catalysis; N-heterocyclic carbenes; synthesis

(untitled) - Marcon, G.; Messori, L.; Orioli, P. (Expert Rev. Anticancer Ther., 2002)

(untitled) - Hashmi, A. S. K.; Hutchings, G. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Hashmi, A. S. K. (Gold Bull., 2009)

(untitled) - He, X.; Yam, V. W.-W. (Coord. Chem. Rev., 2011)

(untitled) - Liu, L.-P.; Hammond, G. B. (Chem. Soc. Rev., 2012)

(untitled) - Schmidbaur, H.; Schier, A. (Chem. Soc. Rev., 2012)

(untitled) - Gómez-Suárez, A.; Nolan, S. P. (Angew. Chem., Int. Ed., 2012)

(untitled) - Díez-González, S.; Marion, N.; Nolan, S. P. (Chem. Rev., 2009)

(untitled) - Nelson, D. J.; Nolan, S. P. (Chem. Soc. Rev., 2013)

(untitled) - de Frémont, P.; Marion, N.; Nolan, S. P. (Coord. Chem. Rev., 2009)

(untitled) - Marion, N.; Nolan, S. P. (Chem. Soc. Rev., 2008)

(untitled) - Nolan, S. P. (Acc. Chem. Res., 2011)

(untitled) - Collado, A.; Gómez-Suárez, A.; Martin, A. R.; Slawin, A. M. Z.; Nolan, S. P. (Chem. Commun., 2013)

(untitled) - Gaillard, S.; Slawin, A. M. Z.; Nolan, S. P. (Chem. Commun., 2010)

(untitled) - Gómez-Suárez, A.; Ramón, R. S.; Slawin, A. M. Z.; Nolan, S. P. (Dalton Trans., 2012)

(untitled) - Dupuy, S.; Slawin, A. M. Z.; Nolan, S. P. (Chem.–Eur. J., 2012)

(untitled) - Dupuy, S.; Crawford, L.; Bühl, M.; Slawin, A. M. Z.; Nolan, S. P. (Adv. Synth. Catal., 2012)

(untitled) - Dupuy, S.; Lazreg, F.; Slawin, A. M. Z.; Cazin, C. S. J.; Nolan, S. P. (Chem. Commun., 2011)

(untitled) - Fortman, G. C.; Poater, A.; Levell, J. W.; Gaillard, S.; Slawin, A. M. Z.; Samuel, I. D. W.; Cavallo, L.; Nolan, S. P. (Dalton Trans., 2010)

(untitled) - Gaillard, S.; Rix, D.; Slawin, A. M. Z.; Lacour, J.; Nolan, S. P. (Dalton Trans., 2012)

(untitled) - Konkolewicz, D.; Gaillard, S.; West, A. G.; Cheng, Y. Y.; Gray-Weale, A.; Schmidt, T. W.; Nolan, S. P.; Perrier, S. (Organometallics, 2011)

(untitled) - Gaillard, S.; Nun, P.; Slawin, A. M. Z.; Nolan, S. P. (Organometallics, 2010)

(untitled) - Egbert, J. D.; Slawin, A. M. Z.; Nolan, S. P. (Organometallics, 2013)

(untitled) - Johnson, M. W.; Shevick, S. L.; Toste, F. D.; Bergman, R. G. (Chem. Sci., 2013)

(untitled) - Newcombe, S.; Bobin, M.; Shrikhande, A.; Gallop, C.; Pace, Y.; Yong, H.; Gates, R.; Chaudhuri, S.; Roe, M.; Hoffmann, E.; Viseux, E. M. E. (Org. Biomol. Chem., 2013)

(untitled) - Boogaerts, I. I. F.; Nolan, S. P. (J. Am. Chem. Soc., 2010)

(untitled) - Vogler, A.; Kunkely, H. (Coord. Chem. Rev., 2001)

(untitled) - Ito, H.; Saito, T.; Oshima, N.; Kitamura, N.; Ishizaka, S.; Hinatsu, Y.; Wakeshima, M.; Kato, M.; Tsuge, K.; Sawamura, M. (J. Am. Chem. Soc., 2008)

(untitled) - Carlos Lima, J.; Rodriguez, L. (Chem. Soc. Rev., 2011)

(untitled) - Lu, W.; Kwok, W.-M.; Ma, C.; Chan, C. T.-L.; Zhu, M.-X.; Che, C.-M. (J. Am. Chem. Soc., 2011)

(untitled) - Cámara, J.; Crespo, O.; Gimeno, M. C.; Koshevoy, I. O.; Laguna, A.; Ospino, I.; Smirnova, E. S.; Tunik, S. P. (Dalton Trans., 2012)

(untitled) - Partyka, D. V.; Teets, T. S.; Zeller, M.; Updegraff, J. B.; Hunter, A. D.; Gray, T. G. (Chem.–Eur. J., 2012)

(untitled) - Heckler, J. E.; Zeller, M.; Hunter, A. D.; Gray, T. G. (Angew. Chem., Int. Ed., 2012)

(untitled) - Gao, L.; Partyka, D. V.; Updegraff, J. B., III; Deligonul, N.; Gray, T. G. (Eur. J. Inorg. Chem., 2009)

(untitled) - Hirtenlehner, C.; Krims, C.; Hölbling, J.; List, M.; Zabel, M.; Fleck, M.; Berger, R. J. F.; Schoefberger, W.; Monkowius, U. (Dalton Trans., 2011)

(untitled) - To, W.-P.; Tong, G. S.-M.; Lu, W.; Ma, C.; Liu, J.; Chow, A. L.-F.; Che, C.-M. (Angew. Chem., Int. Ed., 2012)

(untitled) - Gimeno, M. C.; Laguna, A.; Visbal, R. (Organometallics, 2012)

(untitled) - Visbal, R.; Ospino, I.; López-de-Luzuriaga, J. M.; Laguna, A.; Gimeno, M. C. (J. Am. Chem. Soc., 2013)

WO Patent - Fujimura, O.; Fukunaga, K.; Honma, T.; Machida, T. (Substituted phenylethynyl gold-nitrogenated heterocyclic carbene complex, 2004)

WO Patent - Fujimura, O.; Fukunaga, K.; Honma, T.; Machida, T. (Gold complex, method for production of the gold complex, and organic ultraviolet electroluminescent element using the gold complex, 2008)

Jpn Patent - Fujimura, O.; Fukunaga, K.; Honma, T.; Machida, T. (Substituted phenylethynyl gold-nitrogen-containing heterocyclic carbene complex, 2008)

(untitled) - Zhao, Y.; Truhlar, D. G. (Acc. Chem. Res., 2008)

Gaussian 03, Revision D.02 (Gaussian Inc., 2004)